Operative Management of Adult Spinal Deformity Results in Significant Increases in QALYs Gained Compared to Nonoperative Management: Analysis of 479 Patients With Minimum 2-Year Follow-Up. Issue 5 (1st March 2018) - Scheer, Justin K.; Hostin, Richard; Robinson, Chessie; Schwab, Frank; Lafage, Virginie; Burton, Douglas C.; Hart, Robert A.; Kelly, Michael P.; Keefe, Malla; Polly, David; Bess, Shay; Shaffrey, Christopher I.; et al.
Abstract : Study Design: Retrospective review of prospective multicenter adult spinal deformity (ASD) database. Objective: To compare the quality-adjusted life years (QALYs) between operative and nonoperative treatments for ASD patients. Summary of Background Data: Operative management of ASD repeatedly demonstrates improvements in HRQOL over nonoperative treatment. However, little is reported regarding QALY improvements after surgical correction of ASD. Methods: Inclusion criteria: ≥18 years, ASD. Health utility values were calculated from SF6D scores and used to calculate QALYs at minimum 2 years from the baseline utility value as well as at 1, 2, and 3 years for the available patients. A 1:1 propensity score matching using six baseline variables was conducted to account for the nonrandom distribution of operative and nonoperative treatments. Results: Four hundred seventy-nine patients were included (OP:258, 70.7%, NONOP:221, 47.1%). One hundred fifty-one (OP:90, NONOP:61) had complete 1, 2, and 3 year data available for QALY trending. Unmatched results are not listed in the abstract. Mean baseline utility scores were statistically similar between the matched groups (OP: 0.609 ± 0.093, NONOP: 0.600 ± 0.091, P = 0.6401) and at 2 year min postop mean OP QALY was greater than NONOP (1.377 ± 0.345 vs. 1.256 ± 0.286, respectively, P < 0.01). For the subanalysis cohort, mean OP QALYs at 1, 2, and 3 years postoperative were all significantly greater than NONOP, P < 0.03 for all (1 yr: 0.651 ± 0.089 vs. 0.61 ± 0.079, 2 yr: 1.29 ± 0.157 vs. 1.189 ± 0.141, and 3 yr: 1.903 ± 0.235 vs. 1.749 ± 0.198, respectively). Matched OP had a larger QALYs gained (from baseline) at 2 year minimum postoperative (0.112 ± 0.243 vs. 0.008 ± 0.195, P < 0.01). For subanalysis of patients with complete 1 to 3 years data, OP had a significantly larger QALYs gained at 1, 2, and 3 years compared with NONOP: 1 year (0.073 ± 0.121 vs. 0.029 ± 0.082, P = 0.0447), 2 years (0.167 ± 0.232 vs. 0.036 ± 0.173, P = 0.0030), and 3years (0.238 ± 0.379 vs. 0.059 ± 0.258, P < 0.01). Conclusion: The operative treatment of adult spinal deformity results in significantly greater mean QALYs and QALYs gained at minimum 2 years postop as well as at the 1-, 2-, and 3-year time points compared with nonoperative management. Level of Evidence: 3